Tolerance in the Piil Pesenggiri of Lampung Society - Mujiyati, Mujiyati (Universitas Pendidikan Indonesia, 2018)
This study aims to produce a description within the meaning of tolerance in piil pesenggiri Lampung society. The scope of the study includes: 1) an overview of tolerance of Lampung society; 2) Description of the meaning of tolerance in piil pesenggiri Lampung society; 3) the value of tolerance in guidance and counseling. This research uses a qualitative approach with the descriptive method. Participants were determined by purposive sampling, among other's traditional leaders (one person), community leaders (two people), and academics (three people) engaged in research in Lampung society. The research conducted, namely: 1) researchers construct the meaning of tolerance in pill pesenggiri passenger based on theory and research results; 2) the researcher clarifies to the participants (customary figures, community leaders, and academics) to constructions made through interviews; 3) the researcher performs data analysis by data reduction; and 4) the researcher conducts an interpretation of the constructs based on upon the results of the data analysis. Based on the results of data interpretation, the resulting definition of tolerance in piil pesenggiri is the recognition of the rights of others that are different from the cultural norms of Lampung culture applied in social life in the form of appreciating the difference, open and accept the opinions of others, caring, and give freedom to others in acting.